Structure–Activity Relationships for Side Chain Oxysterol Agonists of the Hedgehog Signaling Pathway - Corman, Audrey (American Chemical Society, 2012)
[Image: see text] Oxysterols (OHCs) are byproducts of cholesterol oxidation that are known to activate the Hedeghog (Hh) signaling pathway. While OHCs that incorporate hydroxyl groups throughout the scaffold are known, those that act as agonists of Hh signaling primarily contain a single hydroxyl on the alkyl side chain. We sought to further explore how side chain hydroxylation patterns affect oxysterol-mediated Hh activation, by performing a structure–activity relationship study on a series of synthetic OHCs. The most active analogue, 23(R)-OHC (35), demonstrated potent activation of Hh signaling in two Hh-dependent cell lines (EC(50) values 0.54–0.65 μM). In addition, OHC 35 was approximately 3-fold selective for the Hh pathway as compared to the liver X receptor, a nuclear receptor that is also activated by endogenous OHCs. Finally, 35 induced osteogenic differentiation and osteoblast formation in cultured cells, indicating functional agonism of the Hh pathway.